Are prayer-based interventions effective pain management options? A systematic review and meta-analysis of randomized controlled trials - Jarego, M.; Ferreira-Valente, A.; Queiroz-Garcia, I.; Day, Melissa A.; Pais-Ribeiro, J.; Costa, R. M.; Pimenta, F.; Jensen, M. P. (Journal of Religion and Health, 2023)
This review examined the effects of private and communal participatory prayer on pain. Nine databases were searched. Six randomized controlled trials were included. For private prayer, medium to large effects emerged for 67% to 69% of between-group comparisons; participants in the prayer condition reported lower pain intensity (0.59 < d < 26.17; 4 studies) and higher pain tolerance (0.70 < d < 1.05; 1 study). Pre- to post-intervention comparisons yielded medium to large effects (0.76 < d < 1.67; 2 studies); pain intensity decreased. Although firm conclusions cannot be made because meta-analysis was based on only two studies, the analysis suggested prayer might reduce pain intensity (SMD = − 2.63, 95% CI [− 3.11, − 2.14], I = 0%). (PROSPERO: CRD42020221733).